The Capacity And Capability Of A Rural Primary School In Sabah In Promoting The Teaching And Learning Of The English Language - Lim, Bridget Suk Han (2012)
This study was encouraged by the mobilization of the NKRA (National Key Result Areas) Project specifically the High Performing Schools issue. In essence, this is an investigation of the “live-life” of a rural primary school, School X which rested in rustic Sabah, Malaysia. The performance of the school in the UPSR (Primary School Achievement Test) had been very poor particularly in the English language. The main question posed for this study was “Does a small bucolic school with all its pastoral and rustic conditions have the potential to be a high performing school especially in the English language?” Every school has a life of its own which makes up of different structures and processes.